Empowering English Language Learners with Quizizz Application at SMPN 3 Pancarijang - Andi Nur Aisyah; Andi Asrifan; Buhari Buhari; Sam Hermansyah (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2024)
This study aims to enhance the English language learning experience for students at SMPN 3 Pancarijang using the Quizizz application, an AI-based educational tool. The research employs a quantitative approach to provide empirical evidence on the effectiveness of Quizizz in improving students' English comprehension. By integrating AI technology into the classroom, the study seeks to create an engaging and effective learning environment that motivates students and increases their participation. The research involved a field experiment with class VIII students, utilizing pre- and post-tests, along with surveys to gather data on students' perceptions and learning outcomes. The findings indicate significant improvements in English comprehension and heightened student motivation and engagement. The results suggest that incorporating AI technology like Quizizz can substantially enhance the learning process, demonstrating the potential benefits of integrating advanced educational technologies in secondary education. This study underscores the need for adopting innovative tools in education to improve overall student performance and engagement.